rSIG combined with NLR in the prognostic assessment of patients with multiple injuries - Wei Dan; Liu Xing; Gu Yanlai; Fu Qiuhong; Tang Hua (Open Medicine)
To investigate the significance of the reverse shock index multiplied by the Glasgow Coma Scale score (rSIG) and the neutrophil–lymphocyte ratio (NLR) in the prediction of prognosis in patients with multiple injuries.